Pleomorphic Undifferentiated Uterine Sarcoma in a Young Patient Presenting With Elevated Beta-hCG and Rare Variants of Benign Leiomyoma: A Case Report and Review of the Literature. (July 2020) - Krishnan, Vimal; Sauthier, Philippe; Provencher, Diane; Rahimi, Kurosh
Abstract : Leiomyosarcoma (LMS) is a malignant mesenchymal neoplasm showing smooth muscle differentiation. Uterine LMS is more frequent that nonuterine LMS, and represents 1% of all malignant neoplasms of the uterus. Pleomorphic undifferentiated uterine sarcoma is a rare entity, and is defined by high-grade sarcoma histology with loss of muscular markers. Several cases of pleomorphic undifferentiated uterine sarcoma have been reported in the literature, with worse clinical outcome when compared with conventional LMS. Here we report the first case of a pleomorphic undifferentiated uterine sarcoma in association with LMS in a 33 yr old woman. The patient presented clinically with recurrent vaginal bleeding and suspicion of a trophoblastic tumor. Ancillary testing revealed moderately elevated beta-hCG (49.7 U/L) and no metastatic disease on imaging. Gross examination of the hysterectomy specimen revealed a large heterogenous necrotic uterine mass infiltrating <50% of the myometrium. Microscopic evaluation showed pleomorphic undifferentiated uterine sarcoma adjacent to a nodule of leiomyoma with bizarre nuclei, with loss of myogenic markers in the high grade component. Other findings included a foci of conventional LMS, and diffuse uterine leiomyomatosis. Although beta-hCG dropped to normal levels during follow-up, the patient developed metastatic lesions to the lung at 6 mo postop. Initial elevation of beta-hCG may have correlated with the aggressive histology of the tumor, as reported by some groups previously. Recognition of pleomorphic undifferentiated uterine sarcoma and its distinction from conventional LMS is essential for patient prognosis and management.